Criminalistic Issues of Public Prosecution Defense - Chakhoyan, Artur (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article is devoted to the study of theoretical issues of the system of forensic science.In the article, the author has deeply investigated: the third section of the system of forensic science, which for many years has been traditionally called "investigation tactics", the historical aspects and current state of the tactics of public prosecution defense, as well as the current issues and development prospects of the tactics of public prosecution defense.For this purpose, the author has studied, discussed and analyzed the opinions and viewpoints contained in the works of both domestic and foreign criminologists-scientists on this issue.The need to develop forensic instructions for the effective defense of public prosecution is currently, in the author's opinion, no longer a controversial scientific issue, since it has been substantiated and is conditioned not only by the needs of theory, but also by the practice of judicial investigation.As a result of the research, the author has briefly presented the essence and system of the tactics of public prosecution defense in the article.
Keywords: the criminalistics system; investigative tactics; criminalistic tactics; judicial tactics; public accusation; defense of the accusation; prosecutor; public prosecutor